MENINGKATKAN KEPATUHAN WAJIB PAJAK MELALUI KUALITAS PELAYANAN - SUPADMI, NI LUH (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 2 (2009), 2009)
Self assessment system of Indonesian taxation demands highlevel of taxpayers’ awareness and compliance in fulfilling tax liabilitiesin order to increase state revenue from taxation sector. The level ofcompliance could be increased through providing better service qualityby the taxation office, which includes safety, comfort, and quickservices, as well as law enforcement. Taxpayers’ compliance level couldbe measured by examining whether they understand taxation law, fillin tax form completely and clearly, calculate tax liabilities correctly, andreport tax liabilities timely.
Keywords: compliance, taxpayers, service quality, tax revenue